Development of White Spruce Tree Islands in the Shrub Zone of the Forest-tundra - Scott, Peter A.; Hansell, Roger I.C. (ARCTIC, 2002)
The growth of four white spruce (Picea glauca) clonal islands ranging in age from ca. 98 years to more than 400 years was investigated in the shrub zone of the forest-tundra east of Churchill, Manitoba, Canada. The elongation of 20 similar-aged stems in each of the three youngest islands was monitored during 1988 and 1989, along with ground and air temperatures. Stems in the younger islands showed a more flexible response to both daily and annual variation in temperature. Younger islands showed faster recovery from frost events during elongation and longer periods of elongation in cooler years. Early spring warming that caused snowmelt to occur before the growing season appeared to result in moisture stress later in the period of elongation. In stems of spruce shrub, the branches are concentrated near ground level because growth is slow and adventitious buds develop on the stem after repeated loss of stem terminals through snow abrasion. In young trees, shading and increased moisture from trapped snow coincide with feather moss establishment and a deep active layer, resulting in higher ground temperatures and faster tree growth. It is during this early period of development that a tree may be best able to develop an erect stem. In later development, the lowest branches of trees become appressed, grow roots, and become second-order stems, and this process continues outward from the central stem. In older tree islands, peat accumulation and needle abrasion can lead to conditions less favourable for growth and maintenance of needles. Consequently, the canopy may thin, which reduces its ability to trap snow. When snow cover is reduced, lichen-heath establishes and permafrost intrudes into the mound. Subsequent growth of the secondary stems on the mound may be too slow to enable successful development of an erect stem. Thus, island development is largely dependent on changing ground temperatures, which become colder as peat accumulates and frost heaving elevates the mound. Warm spring and summer conditions appear to ...